Agricultural extension services in Bangladesh: experiences of vulnerability, access, and benefits - Joshi, Deepa; Panagiotou, A.; Rahman, M. W. (International Water Management Institute, 2024)
Bangladesh, one of the world's most densely populated countries, faces significant challenges related to poverty, food insecurity, and agricultural productivity. With over 40% of the population engaged in agriculture, the majority of which involves smallholder rice farming, these challenges are even more pronounced. Approximately 92% of farmers own less than 0.5 hectares of land, making it difficult for them to achieve sustainable incomes. While efforts like irrigation and triple-cropping aim to intensify crop production, they often fail to ensure economic stability, especially in climate-vulnerable coastal regions. Farmers in these areas frequently resort to seasonal migration and face severe economic distress. Given these conditions, agricultural innovation and access to extension services are crucial for improving food security and farmer livelihoods. However, adoption of new agricultural practices remains low, especially among women, due to challenges such as low literacy, cultural norms, and limited social mobility.